International conference on physiological and cognitive performance in extreme environments, 27-3o March 2000 (Australian Institute of Sport, 2000)
INVITED LECTURE 1: EXERCISE, HEAT STRESS AND FATIGUE M. Hargreaves 1 PAPER 1: THE INFLUENCE OF WHOLE BODY VS TORSO PRE-COOLING ON PHYSIOLOGICAL STRAIN AND PERFORMANCE OF HIGH INTENSITY EXERCISE IN THE HEAT. G.G. Sleivert, J.D. Cotter, W.S. Roberts and M.A Febbraio 4 PAPER 2: THE INFLUENCE OF TORSO AND WHOLE-BODY PRE-COOLING ON STRAIN AND PERFORMANCE DURING ENDURANCE WORK IN THE HEAT. J.D. Cotter, G.G. Sleivert, W.S. Roberts and M.A Febbraio 8 INVITED LECTURE 2: HEAT STRESS AND EXERCISE METABOLISM M.A Febbraio 12 PAPER 3: EFFECT OF ENVIRONMENTAL TEMPERATURE ON STEADY-STATE AND MAXIMAL CYCLING J.P. Finn, J.F. Marsden, R.J. Wood and AL. Travar 17 INVITED LECTURE 3: HYDRATION EFFECTS ON THERMOREGULATION AND PERFORMANCE IN THE HEAT M.N. Sawka 21 PAPER 4: THE EFFECT OF GLYCEROL HYPERHYDRATION ON OLYMPIC DISTANCE TRIATHLON PERFORMANCE IN HIGH THERMAL STRESS. A Coutts, P. Reaburn and K Mummery 24 PAPER 5: THE MAIN FUNCTION OF THERMOREGULATION AND THE SUBJECT OF TEMPERATURE CONTROL KP.Ivanov 28 INVITED LECTURE 4: SWEATING IN EXTREME ENVIRONMENTS: HEAT LOSS, HEAT ADAPTATION, BODY-FLUID DISTRIBUTION AND THERMAL STRAIN. N.AS. Taylor 32 PAPER 6: TO WHAT EXTENT DOES THERMAL SENSATION REFLECT PHYSIOLOGICAL HEAT STRAIN S. Baker, and J. Grice 36 INVITED LECTURE 5: PARTICIPATION OF GASTROINTESTINAL ENDOTOXINS IN THE TOLERANCE OF HEAT AND EXERCISE J.R.S. Hales and S. Sakurada 42 PAPER 9: INTER-RELATIONSHIPS BETWEEN SWEATING, CORE AND INTRAMUSCULAR TEMPERATURES. G. Russell, D.P.Y. Koonen, T. Heemskerk, D. Hennekens, H. Groeller and N.AS. Taylor 48 INVITED LECTURE 6: TIME COURSE OF HEAT ACCLIMATION AND ITS RETENTION KB.Pandolf 51 PAPER 10: URINALYSES AND BODY MASS CHANGES DURING AN ULTRADISTANCE ENDURANCE EVENT: THE SIMPSON DESERT CYCLE CHALLENGE P. Reaburn and A. Coutts 56 INVITED LECTURE 7: HUMAN HEAT ACCLIMATION: WHAT IS THE BEST METHOD? RWithey 60 PAPER 11: THE THERMOREGULATORY STRAIN PRODUCED BY PROTECTIVE PVC SUITS DURING SIMULATED CHEMICAL SPILL CLEAN-UP OPERATIONS IN A HOT ENVIRONMENT IS NOT REDUCED BY PASSIVE COOLING VESTS. R. Holdsworth and M. Crowe 61 PAPER 12: ENHANCEMENT OF PERFORMANCE THROUGH HEAT ACCLIMATION AND RACE SIMULATION AMONGST MOTORSPORT ATHLETES S.M. Walker, B. Dawson and T.R. Ackland 65 INVITED LECTURE 8: THE IMPORTANCE OF AEROBIC FITNESS IN DETERMINING TOLERANCE TO UNCOMPENSABLE HEAT STRESS T.M.McLellan 68 PAPER 13: THE EFFECTS OF WEARING SUNSCREEN LOTION ON HERMOREGULATORY RESPONSES DURING EXERCISE IN THE HEAT IN ADULT AND ADOLESCENT MALES. G. Naughton, J. Carlson, M. Gibbs and R. Snow 72 PAPER 14: WHOLE-BODY PRE-COOLING: THERMAL, CARDIOVASCULAR AND METABOLIC CONSEQUENCES. A.D. MacDonald, J. Booth, A.L. Fogarty, K.A. Armstrong, H. Groeller, A. Hahn, L.H. Storlien and N.A.S. Taylor 76 PAPER 15: ENHANCED CUTANEOUS BLOOD FLOW AND HEAT OF SORPTION AFTER THE ONSET OF SWEATING DURING HEAT LOAD K. Tanaka and K. Hirata 80 INVITED LECTURE 9: NUTRITIONAL NEEDS IN THE HEAT L. Burke 83 PAPER 16: EXERCISE NORTHERN AWAKENING: NUTRITION STUDY C. Booth, R Coad, C. Forbes-Ewan, G. Thomson, P. Davies and P. Niro 86 PAPER 17: DO CAFFEINE AND EPHEDRINE HAVE A BENEFICIAL IMPACT ON HUMAN PERFORMANCE DURING PROLONGED EXPOSURE TO A COLD, WET AND WINDY ENVIRONMENT? A.S. Weller, E.M. O'Connor, V.R. Nevola, and M.H. Harrison 89 INVITED LECTURE 10: AN EVALUATION OF THE CONCEPT OF LIVING AT MODERATE ALTITUDE AND TRAINING NEAR SEA LEVEL A.G. Hahn, CJ. Gore, D.T. Martin, MJ. Ashenden, A.D. Roberts and P.A. Logan. 92 PAPER 18: CLOTHING INSULATION AND THERMAL COMFORT OF TENT OCCUPANTS AT HIGH ALTITUDE K. Cena and P. Tapsell 98 PAPER 19: EFFECTS OF COLD ON MANUAL PERFORMANCE IN SUBJECTS WITH RAYNAUD'S PHENOMENON S. Rissanen, J. Hassi, K. Juopperiand H. Rintamäki 102 INVITED LECTURE 11: EXERTION-INDUCED FATIGUE AND THERMOREGULATION IN THE COLD A.J. Young and J.W. Castellani 105 PAPER 20: RELATIONSHIP BETWEEN MANUAL PERFORMANCE, EXTREMITY TEMPERATURES, AND RATE OF BODY HEAT STORAGE DURING COLD EXPOSURE M.B. Ducharme, D. Brajkovic and J. Frim 109 PAPER 21: THE EFFECTS OF WIND ON THERMAL RESPONSES DURING LIGHT AND MODERATE EXERCISE IN THE COLD T. Mäkinen, D. Gavhed, I. Holm6r, H. Rintamäki 112 PAPER 22: EVIDENCE OF SHIVERING FATIGUE: VERIFICATION OF A PREDICTION MODEL P. Tikuisis, DA Eyolfson, X. Xu, and G.G. Giesbrecht 115 INVITED LECTURE 12: PSYCHOPHYSIOLOGICAL ASPECTS OF COGNITION: TOWARDS AN UNDERSTANDING OF PERFORMANCE IN EXTREME ENVIRONMENTS RJ.Bairy 118 PAPER 23: ANS AND CNS EFFECTS OF LIMB IMMERSION IN ICE COLD WATER R.D. O'Donohue, R.J. Barry and B.P. Corless 122 PAPER 24: HEART RATE VARIABILITY AS A MEASURE OF COGNITIVE WORKLOAD D. Foran, M. Skinner and S. Smith 126 PAPER 25: PSYCHOMETRIC ASSESSMENT OF THE EFFECTS OF THERMAL STRAIN ON COGNITION C. Hocking, R. Silberstein, W.M. Lau, W. Roberts, C. Stough and D. Amos 130 INVITED LECTURE 13: MARKSMANSHIP AND SENTRY DUTY PERFORMANCE UNDER EXTREME ENVIRONMENTS R.F. Johnson 133 PAPER 26: COGNITIVE PERFORMANCE AND PHYSICAL STRESSORS IN EXTREME ENVIRONMENTS R. Brandeis 137 PAPER 27: BRAIN ELECTRICAL ACITVITY MAPPING AND THE EFFECTS OF THERMAL STRAIN ON A SPATIAL WORKING MEMORY TASK C. Hocking, R. Silberstein, W.M. Lau, W. Roberts, C. Stough and D. Amos 141 INVITED LECTURE 14: THE MEASUREMENT OF THERMAL STRAIN IN SOLDIERS OPERATING IN NORTHERN AUSTRALIA D.Amos 144 PAPER 28: THERMAL STRESS AND PERSONAL COOLING SYSTEM P. Bandopadhayay, W.M. Lau and D. Amos 152 PAPER 29: EVALUATION ON THE COOLING SYSTEMS OF AIRTIGHT SUITS USED IN THE CLOSED ECOLOGY EXPERIMENTAL FACILITIES N. Kakitsuba, N. Watanabe and Y. Shirane 155 INVITED LECTURE 15: PREDICTIVE MODELING: ITS USE IN FORECASTING HUMAN RESPONSES TO THE ENVIRONMENT R.R. Gonzalez 159 PAPER 30: THE CONTRIBUTION OF SOLAR RADIATION TO HEAT STRESS AND HEAT STRAIN DURING WORK IN ENCAPSULATING PROTECTIVE SUITS S.E. Atkinson and G.V. Coles 163 PAPER 31: THE DISCOMFORT INDEX PREDICTS THE PHYSIOLOGICAL STRAIN ASSOCIATED WITH INDOOR SPORTS HEAT STRESS R.D. Hansen 167 PAPER 32: OCCUPATIONAL HEAT ILLNESS: AN INTERVENTIONAL STUDY R.J. Brake and G.P. Bates 170 POSTER 1: NECK MUSCLE FATIGUE ISSUES RELATED TO NIGHT VISION GOGGLE USE C. Brady and V. Demczuk 173 POSTER 3: THE EFFECTIVENESS OF AN ICE VEST OR INTRAVENOUS ADMINISTRATION OF FLUID ON RECOVERY FROM HIGH HEAT STRAIN. J.D. Cotter, G.G. Sleivert and W.S. Roberts 179 POSTER 4: EFFECT OF ENVIRONMENTAL TEMPERATURE ON THE ANAEROBIC CAPACITY OF HEAT ACCLIMATISED ATHLETES J.P. Finn, J.F. Marsden, R.J. Wood and AX. Travar 183 POSTER 6: USE OF SENSORS TO STUDY THE MICROCLIMATE WITHIN A CLOTHING ENSEMBLE P. Forshaw 189 POSTER 7: IMPACT OF PERSONAL COOLING SUITS ON AN INFANTRY ATTACK SCENARIO W. Hobbs, T. Castles and M. French 191 POSTER 8: ORIGIN AND REGULATION OF METABOLIC HEAT KP. Ivanov 195 POSTER 9: RESTORATION OF PHYSIOLOGICAL FUNCTIONS IN A COOLED ORGANISM WITHOUT REWARMING THE BODY KP. Ivanov 199 POSTER 10: THE EFFECT OF AIR GAP ON THE FABRIC SURFACE APPARENT TEMPERATURE AND ITS THERMAL RESISTANCE B.Lee 203 POSTER 11: MICROCLIMATE OF THE SMI TANK IN STATIONARY CONDITION L.C. Leong, E. Song and S.B. Kee 207 POSTER 12: IMPROVING THE MILITARY'S WET WEATHER GARMENT DJ. Robinson and G.T. Egglestone 210 POSTER 13: PREDICTION OF THERMAL STRAIN USING NEURAL NETWORKS P.J. Sanders and W.M. Lau 213 POSTER 14: THE COMBINED EFFECT OF HEAT AND CARBON MONOXIDE ON THE PERFORMANCE OF THE MOTORSPORT ATHLETE S.M. Walker, T.R. Ackland and B. Dawson 217